Polymeric nanoparticles containing rapamycin and autoantigen induce antigen-specific immunological tolerance for preventing vitiligo in mice - Xia Zhang; Daji Liu; Minghong He; Mao Lin; Caixia Tu; Baoxiang Zhang (Taylor & Francis Group, 2021)
Vitiligo is an autoimmune disease in which pigment is lost in patches of the skin. CD4+ T cells are implicated in vitiligo while regulatory T cells (Tregs) could ameliorate vitiligo. Rapamycin together with autoantigen have been shown to induce immunological tolerance and promote Tregs in multiple autoimmune diseases. In the current study, we synthesized nanoparticles containing rapamycin and autoantigen HEL46-61 (NPHEL46-61/Rapa) and investigated their effects on vitiligo. We treated bone marrow-derived dendritic cells (BMDCs) from TrpHEL mice with NPHEL46-61/Rapa and monitored the phenotype of BMDCs. We investigated the effects of NPHEL46-61/Rapa-treated BMDCs on CD4+ T cell proliferation and differentiation. We administrated NPHEL46-61/Rapa to TCR-TrpHEL mice and investigated the effects on vitiligo. We found that BMDCs can uptake the NPHEL46-61/Rapa, which resulted in decreased expression of costimulation molecules CD80 and CD86 in BMDCs. BMDCs treated with NPHEL46-61/Rapa suppressed antigen-specific CD4+ T cell proliferation while promoted the differentiation of these CD4+ T cell to Tregs in vitro. Administration of NPHEL46-61/Rapa to TCR-TrpHEL mice ameliorated vitiligo, promoted Treg production, and suppressed IFN-γ and IL-6 production, while induced IL-10 production. Therefore, our study provides experimental evidence that nanoparticles containing rapamycin and autoantigen could induce antigen-specific immunological tolerance and prevent vitiligo.